2015
DOI: 10.4067/s0717-97072015000200022
|View full text |Cite
|
Sign up to set email alerts
|

The Tautomerism of Pyrazolines (Dihydropyrazoles)

Abstract: The exception to the rule that Δ 3 -pyrazolines are not stable unless both nitrogen atoms are substituted that has been recently published, Tetrahedron Lett. 55, 2208, (2014), has been proved false. By means of GIAO/B3LYP/6-311++G(d,p) calculations, it has been shown that the product is a pyrazole formed by rearrangement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…143,144,170 The first paper 143 20. 144 We devoted a paper 170 to the analysis of two publications by Hamme II et al and these are summarized in Scheme 56. 171,172 Scheme 56.…”
Section: Computational Resultsmentioning
confidence: 99%
“…143,144,170 The first paper 143 20. 144 We devoted a paper 170 to the analysis of two publications by Hamme II et al and these are summarized in Scheme 56. 171,172 Scheme 56.…”
Section: Computational Resultsmentioning
confidence: 99%
“…Thus, the major compound 6a proved to be the 16α-H, 17α-H compound while 6b was the 16β-H,17β-H diastereomer (Scheme 1). This can be explained by the tendency of 1-unsubstituted Δ 2 -pyrazolines, such as 4 , to tautomerize under heating or in the presence of an acid [38], and the driving force of the tautomeric equilibrium to be shifted toward 4 - T 3 is the extended conjugation, especially in product 6 after acetylation. A significant difference (Δ δ = 0.37) between the chemical shift values of the equivalent protons of 18-CH 3 was actually observed by comparing the 1 H-NMR spectra of 6a and 6b .…”
Section: Resultsmentioning
confidence: 99%
“…2). Tautomerism of pyrazolines is possible and it was reported that tautomer I is more stable than tautomer II, as shown in Figure 2 (Alkorta and Elguero, 2015).…”
Section: Introductionmentioning
confidence: 96%